PENGARUH NILAI TUKAR DAN INFLASI TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN LQ45 - Pramitha, Anasthasia; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to find out whether the fluctuation of foreign exchange rate and inflation rate give influence to the dividend payout ratio by using nett profit as the intervening variable.The population is all companies which are listed in LQ45 in 2008-2015 periods whereas the samples are 7 companies which always exist in LQ 45 lists during the observation period. The data has been obtained from the secondary data i.e. IDX and Statistics Indonesia and the data has been analyzed by using path analysis and causal step.The result of the analysis shows that the fluctuation of foreign exchange rate and inflation rate does not give direct influence to the dividend payout ratio but through the nett profit as the intervening variable, it is shown by the the t test that the fluctuation of foreign exchange rate and inflation rate give significant influence to the nett profit but it does not give any influence to the dividend payout ratio. The result of the research has proved that nett profit has firm correlation with dividend payout ratio.Keywords: Exchange rate, nett profit, inflation ratio